Prospect in Pediatric Diseases Medicine - Pokorski, Mieczyslaw (Neuroscience and Respiration, 2016)
Good health and medical care in childhood and adolescence are essential for the ability to neutralize health threats later in life and to extend longevity. Thus, pediatric diseases, diagnostics and treatment justifiably draw ever increasing attention. The book highlights recent advances and innovations in gastroesophageal ailments, often missed in children, respiratory infections, and in genetically determined immune malfunctions such as familial hemophagocytic lymphohistiocytosis, known as a cytokine storm, renal vasculitis, or thyroid and growth anomalies. Functional genomics has become part of genetic counseling aimed at early diagnosis and treatment of chromosomal aberrations underlying congenital malformations. Deeper insights into childhood morbidity require identification of the pathways and biological processes most affected which could become drug targets. This book is dedicated to practical aspects of multifactorial disease processes of young age. It will be of interest to pediatricians, family doctors, and clinical researchers.